1985
DOI: 10.1111/j.1768-322x.1985.tb00356.x
|View full text |Cite
|
Sign up to set email alerts
|

MP26 in the bovine lens: a post‐embedding immunocytochemical study

Abstract: Gold immunolabeling of bovine lens tissue embedded in Lowicryl K4M, using a polyclonal antibody specific for a major component of lens fiber plasma membrane of 26 K molecular weight, shows that this constituent is absent from the epithelial cell plasma membrane and associated only with the junctional and non-junctional domains of the lens fiber plasma membrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
1

Year Published

1988
1988
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 0 publications
1
4
1
Order By: Relevance
“…Alternately, this punctate staining could reflect regions of higher protein concentration. The distribution of antibody binding sites is thus most compatible with the view that MIP is present in both the nonjunctional and the junctional membrane, as proposed from immunocytochemical studies by electron microscopy of intact lenses (Fitzgerald et al, 1983;Vallon et al, 1985) and of isolated junctions (Bok et al, I982; Sas et al., 1985). Interestingly, Paul and Goodenough (1983a) also found that by immunofluorescence MIP appeared to be present throughout the fiber cell membrane, junctional and nonjunctional, but failed to detect it in junctions in the isolated membranes.…”
Section: Is ?Clip a Gap Junction Protein?supporting
confidence: 78%
See 2 more Smart Citations
“…Alternately, this punctate staining could reflect regions of higher protein concentration. The distribution of antibody binding sites is thus most compatible with the view that MIP is present in both the nonjunctional and the junctional membrane, as proposed from immunocytochemical studies by electron microscopy of intact lenses (Fitzgerald et al, 1983;Vallon et al, 1985) and of isolated junctions (Bok et al, I982; Sas et al., 1985). Interestingly, Paul and Goodenough (1983a) also found that by immunofluorescence MIP appeared to be present throughout the fiber cell membrane, junctional and nonjunctional, but failed to detect it in junctions in the isolated membranes.…”
Section: Is ?Clip a Gap Junction Protein?supporting
confidence: 78%
“…The cells of the anterior epithelium appear to be devoid of either MIP or 13-A1/A3 transcripts at all time points studied. We, as others (Waggoner and Maisel, 1978;Vermorken et al, 1977, Broekhuyse et al, 1979Paul and Goodenough, 1983a;Vallon et al, 1985), also found no suggestion that MIP is present in the membranes of the epithelial cells. This lack of immunostaining of epithelial cell membranes is particularly striking at the early stages of lens morphogenesis before the cells of the posterior wall fill the lumen of the lens vesicle and make solid contact with the anterior epithelial cells.…”
Section: Expression Of the ~-A1/a3 And Mip Genescontrasting
confidence: 43%
See 1 more Smart Citation
“…Furthermore, only thin (13-nm)junctions showed antibody binding, while junctions of normal thickness (17 nm) did not. In contrast, with monoclonal antibodies Fitzgerald, Bok and Horwitz (1982), Sas et al (1985) and Vallon et al (1985) localized MIP26 at both types of junctions.…”
Section: Po(~) -Oz+~"mentioning
confidence: 77%
“…It has also been located in plasma membranes of virtually all nonfenestrated capillary endothelial cells, but is not found in fenestrated capillaries (Nielsen et al 1993b;Sabolic et al 1992). Lens and corneal epithelium, but not lens fibers, which contain MIP26 (Dunia et al 1987;Vallon et al 1985), are also rich in AQP1 (Nielsen et al 1993b;Stamer et al 1994;Verbavatz et al 1994). Recently, several cell types in the inner ear have also been shown to express high levels of AQP1 (Stankovic et al 1995).…”
Section: Introductionmentioning
confidence: 89%